Analysis of The Pentahelix Model on The Development of The Tourism Sector on Majene West Sulawesi - Hendrawan; Rezky Ramadhan Antuli; Muhammad Syihabuddin Taufiq; Rahmatullah; Rezki Rahmawati; Farhanuddin (Kirana Publisher (KNPub), 2023)
The aim of this research is to analyze the pentahelix model in the development of the tourism sector in Majene regency. The type of research used in this research is explanatory research. This research uses data collection techniques in the form of secondary literature studies with qualitative analysis techniques. The end result of this research is a description of the causal context or cause-and-effect relationships. The results of this research show this. The tourism sector in Majene Regency requires the participation of five stakeholders, including: government, private sector, academia, community and media, each of which has a role that, if collaborated well, will produce world-class tourism destinations. However, these five actors need space and regulations formulated in a patented way so that a series of activities can be created as a sustainable program in the context of the development of the tourism sector in Majene Regency